'til Dissolution Do Us Part: (Re)Assessing the First Contract and Trial Marriage Goals of First Contract Arbitration in Ontario. Issue 1 (18th February 2021) - Weinberg, Bradley R.
Abstract : Using a series of labor law reforms in the Canadian province of Ontario between 1991 and1998, this article seeks to (re)assess and compare the effectiveness of two forms of first contract arbitration (FCA) in satisfying the primary policy goals of aiding in the achievement of a first contract and in establishing lasting bargaining relationships. In contrast to previous research findings using this setting, the analysis fails to identify any statistically significant difference in the achievement of first contracts across the automatic and no‐fault forms of FCA. Further, estimates do not appear to identify a statistically significant difference in the establishment of lasting bargaining relationships, defined as the settlement of three of more collective agreements, across the two forms of FCA. These findings indicate that differences observed during this period in the first contract success rate and the establishment of bargaining relationships may be confounded with other factors than the changes to first contract arbitration.